DIALOG FIKIH DAN BUDAYA DALAM KUMANDANG AZAN - AHMAD MUNIF (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This paper attempts to examine the background of prayer calls (adzan) that was influenced by the customs and habits of the local people. Adzan which should be sounded immediately after the prayer time comes was deliberately sounded an hour later by the Muslims in Tlogogedong village, the southern part of Demak district. Though it seems that Muslims in Tlogogedong village do not follow the religious order to perform prayers in early time, this late prayer calls had a deeper purpose. The study finds out that the delayed adzan was intended to accommodate local people to perform another religious order, which is congregated prayers. The delay in prayer calls give more time for local people who work as farmers, for other professions to wait until their break times, and for children to finish their quranic reading activities. with religious texts related to the early morning prayer and congregational prayers. This finding indicates that there was a dialogue between religious order and local practice and situation that can be used an example or model in understanding Islamic texts by adjusting the local culture of a region. KEY WORDS: Adzan, Prayer Time, Dialog, Local Culture